2008
DOI: 10.1007/s10725-008-9353-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectral reflectance indices and pigment functions during leaf ontogenesis in six subtropical landscape plants

Abstract: Pigment combinations are regulated during leaf ontogenesis. To better understand pigment function, alterations in chlorophyll, carotenoid and anthocyanin concentrations were investigated during different leaf development stages in six subtropical landscape plants, namely Ixora chinensis Lam, Camellia japonica Linn, Eugenia oleina Wight, Mangifera indica L., Osmanthus fragrans Lowr and Saraca dives Pierre. High concentrations of anthocyanin were associated with reduced chlorophyll in juvenile leaves. As leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…4 Images of chlorophyll fluorescence parameters (U PSII , NPQ/4 and qP) in P. massoniana (a), S. superba (b) and A. acuminatissima (c) leaf sections after long term light (100 and 12% sunlight) treatments and following shortterm treatments with 50 mM NaHSO 3 solution. Bar along the bottom of images indicates relative value of each parameter as a percentage environment (White and Critchley 1999;Schreiber 2004;Liu et al 2009). In the present study, RLCs were reliant on long-term different natural light intensities and showed distinctions with each other (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…4 Images of chlorophyll fluorescence parameters (U PSII , NPQ/4 and qP) in P. massoniana (a), S. superba (b) and A. acuminatissima (c) leaf sections after long term light (100 and 12% sunlight) treatments and following shortterm treatments with 50 mM NaHSO 3 solution. Bar along the bottom of images indicates relative value of each parameter as a percentage environment (White and Critchley 1999;Schreiber 2004;Liu et al 2009). In the present study, RLCs were reliant on long-term different natural light intensities and showed distinctions with each other (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Baijiguan is more sensitive to high light intensity, of which chloroplast development is retarded, and its chlorophyll content is lower than other green-leaf varieties at the same developmental stage [7]. Chlorophyll plays an essential role in photosynthesis by absorbing and transferring the light energy to other molecules of the photosynthetic electron transport chain [35]. The chlorophyll accumulation in plants is dynamic [36,37], which is a comprehensive process of synthesis and decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the wavelengths individually or simultaneously, optical meters were attached between the leaf mid-vein and edge parts, with the upper leaf pointing upward, as described by Davenport et al (2005). Reflectance spectra were recorded for the upper surfaces of the leaves, inter-veinal areas, or middle parts of the uppermost fully expanded leaves (Wang et al, 2004;Follett et al, 1992;Gitelson et al, 1996;Liu et al, 2009). However, most sampling locations in spectral reflectance measurements described in the literature were selected based on the suggestions in previous works.…”
Section: Introductionmentioning
confidence: 99%